Resistance to extinction versus extinction as discrimination. Issue 3 (15th April 2021) - Bell, Matthew C.; Baum, William M.
Abstract : The hypothesis that response strength might be measured by persistence of responding in the face of extinction was discredited in the 1960s because experiments showed that responding persists longer following intermittent reinforcers than following continuous reinforcers. Instead, researchers proposed that the longer persistence following intermittent reinforcers arises because intermittent reinforcement more closely resembles extinction—a discrimination theory. Attention to resistance to extinction revived because one observation seemed to support the persistence hypothesis: Following training on a multiple schedule with unequal components, responding usually persisted longer in the formerly richer component than in the formerly lean component. This observation represents an anomaly, however, because results with single schedules and concurrent schedules contradict it. We suggest that the difference in results arises because the multiple‐schedule procedure, while including extensive training on stimulus discrimination, includes no training on discrimination between food available and food unavailable, whereas comparable single‐ and concurrent‐schedule procedures include such training with repeated extinction. In Experiment 1, we replicated the original result, and in Experiment 2 showed that when the multiple‐schedule procedure includes training on food/no‐food discrimination, extinction following multiple schedules contradicts behavioral momentum theory and agrees with the discrimination theory and research with single and concurrent schedules.